A potential nanoparticle-loaded in situ gel for enhanced and sustained ophthalmic delivery of dexamethasone. (17th August 2018) - Wen, Yifeng; Ban, Junfeng; Mo, Zhenjie; Zhang, Yan; An, Peigang; Liu, Lizhong; Xie, Qingchun; Du, Youyun; Xie, Baoyin; Zhan, Xiaolong; Tan, Liyao; Chen, Yanzhong; et al.
Abstract: Increasing the permeability of drugs across the cornea is key to improving drug absorption by the eye. This study presents a newly developed in situ gel loaded with nanoparticles, which could achieve controlled drug release and high ocular drug bioavailability by avoiding rapid precorneal clearance. The physicochemical parameters of the formulation were investigated and showed uniform size, physical stability, and favorable rheological and gelling properties. Ex vivo permeation studies revealed significantly higher drug release from the in situ gel loaded with nanoparticles compared to the conventional poloxamer in situ gel and the drug solution. When compared with a marketed formulation, the in situ gel loaded with nanoparticles provided slower controlled release and higher ocular bioavailability of dexamethasone. In conclusion, the developed nanoparticle-loaded in situ gel can successfully increase drug ocular bioavailability by enhancing contact time with the ocular surface and permeation through the cornea.